Studies on mononuclear chelates derived from substituted Schiff-base ligands (Part 10) - Canpolat, Erdal; Yazici, Aysegul; Kaya, Mehmet (Taylor & Francis Ltd, 2007)
In this study, 4-hydroxysalicylaldehyde-p-aminoacetophenoneoxime (LH) was synthesized starting from p-aminoacetophenoneoxime and 4-hydroxysalicylaldehyde. Complexes of this ligand with Co(II), Ni(II), Cu(II) and Zn(II) were prepared with a metal: ligand, ratio of 1 : 2. The ligand and its metal complexes have been characterized by elemental analyses, IR, H-1- and C-13-NMR spectra, magnetic susceptibility measurements and thermogravimetric analyses (TGA).
Keywords: Schiff bases; transition metal complexes; thermogravimetric analyses